Detecção molecular de Ehrlichia canis e de anticorpos da classe IgG contra Ehrlichia canis e Ehrlichia chaffeensis em indivíduos da comunidade acadêmica da Faculdade de Medicina Veterinária da UFMT - Campos, Amanda Noéli da Silva (2022)
The genus Ehrlichia belongs to the order Rickettsiales, classified in the family Anaplasmataceae. Some of these species have public health importance, as they are able to infect humans. Among these agents, Ehrlichia chaffeensis stands out, which causes an important ehrlichiosis in humans and Ehrlichia canis, an important canine pathogen that has been reported in humans. Furthermore, reports of parasitism by R. sanguineus in humans in Brazil enhance the emerging importance of the zoonotic character of Ehrlichia canis infection. People who work with or have close contact with dogs, such as veterinarians, veterinary students, and dog handlers are among the individuals most at risk of contact with the agent. Based on these premises, as the region of Cuiabá is endemic for E. canis, this study aimed to carry out a serological survey of anti-E. canis and E. chaffeensis by means of Indirect Immunofluorescence Reaction (IFRS) and Enzyme Linked Immunosorbent Assay (ELISA); and molecular by means of PCR in 198 individuals from the Faculty of Veterinary Medicine at UFMT, including veterinarians and students. Of the samples evaluated, 14 (7.58%) were reactive to IFAT with titers ≥ 40. ELISA to detect anti-E. canis showed 10 (5.0%) samples were reactive to the TRP19 protein antigen, five (2.5%) to the USTRP36 and BrTRP36 protein, and three (1.5%) to the CrTRP36 3 protein (1.51%). Also by means of ELISA, three (1.5%) individuals showed a reaction against the TRP32 protein of E. chaffeensis. All samples showed negative PCR results for Ehrlichia canis. The detection of antibodies in the population studied reinforces the hypothesis that this group of individuals belongs to the population at risk, frequently exposed to these pathogens. The results of the present study reinforce the zoonotic potential of E. canis agents in the studied region.